Poetic topolectization in the formative years of the Chinese "new poetry" - Yulia A. Dreyzis (Publishing house "Sreda", 2023)
The paper explores the infiltration of topolect into the poetry of Liu Bannong and Crescent Moon Society authors, induced by the Folksong Collection Movement, often labeled as introducing vernacular into poetry. The language of Liu Bannong's New Poetry presents a complex hybrid between the emerging literary norm, local Beijing vernacular and his native lect of the northern Taihu region. Many contemporaries noted his poetry's merits and his invaluable contribution to New Poetry development, greatly facilitated by Liu Bannong's professional linguistic training. Following Liu Ban Nong's footsteps, the Crescent Moon Society suggested experimenting with a new poetic language through the prism of the vernacular. Theorizing was supported by poetic practice: the authors of the Crescent Moon Society included topolect vocabulary in the texts abundantly, and directly marked individual poems as colloquial. In addition to inlaying topolect vocabulary or including large fragments of text written in topolect, topolectization was also carried out through rhyming. Despite the fact that further influence of this topolect poetry remained underestimated, the emerging connection between topolect and the authentic embodiment of the idea of a national language has become important for any discussion about language reform in the new China.